PSYCHOTHERAPY OF THE ELDERLY WITH NON-PSYCHOTIC MENTAL DISORDERS IN CHRONIC CEREBROVASCULAR PATHOLOGY - Rajabov Hikmat Toshevich; Hayatov Rustam Batirbekovich (Research Focus International Scientific Journal, 2023)
Approaches to psychotherapy of elderly people with non-psychotic mental disorders are considered. It is shown that short-term problem-oriented psychotherapeutic methods (rational, behavioral, positive, family psychotherapy) aimed at reducing neurotic symptoms, social support and improving the quality of life are most acceptable for psychotherapy in old age with chronic cerebrovascular pathology.